2015
DOI: 10.1007/s11051-015-3144-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of a shear thickening fluid: the dispersions of silica nanoparticles in 1-butyl-3-methylimidazolium tetrafluoroborate

Abstract: The dispersions was prepared by dispersing hydrophilic silica nanoparticles with an average diameter of 50 nm in 1-butyl-methylimidazolium tetrafluoroborate ([C 4 mim][BF 4 ]), and investigated under the steady shear and oscillatory shear, respectively. Experimental results indicate that all of the dispersions present shear thinning, notable shear thickening, and shear thinning successively with increasing shear rate; the shear thickening behavior is derived from silica nanoparticle clusters and strongly contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…When increased magnetic flux densities from 70 to 210 mT were employed, MRSTPFs behaved as a storage system. This was because the storage modulus got higher than the loss modulus under the 0.1-100 Hz shear frequency [57]. This behavior was consistent with the magnetorheological effect.…”
Section: Dynamic Shear Frequency Sweepssupporting
confidence: 81%
See 1 more Smart Citation
“…When increased magnetic flux densities from 70 to 210 mT were employed, MRSTPFs behaved as a storage system. This was because the storage modulus got higher than the loss modulus under the 0.1-100 Hz shear frequency [57]. This behavior was consistent with the magnetorheological effect.…”
Section: Dynamic Shear Frequency Sweepssupporting
confidence: 81%
“…The storage modulus and loss modulus gradually increased at first when magnetic flux density was 0 mT. This was caused by the balanced status between the generated and the destroyed hydro-clusters [57]. After that, the storage modulus and loss modulus sharply decreased to the critical shear frequency.…”
Section: Dynamic Shear Frequency Sweepsmentioning
confidence: 95%
“…Solid fraction, which is the fraction of the total volume or weight occupied by particles against the whole system, is found to be the most important factor affecting shearthickening. Previous studies have confirmed that increasing particle fraction leads to a decrease in the critical shear rate, and the high fraction dispersion exhibits a greater increase in viscosity [9][10][11]. Moreover, the critical shear rate increases with the increasing particle size, and the maximum viscosity of the suspension increases when decreasing the size and dispersity of particles [12][13][14].…”
Section: Introductionmentioning
confidence: 76%
“…As shown in Fig. 12(d), Qin et al 116 hypothesised that in case of high solid content, shear thickening is dictated by jamming of particles akin to a logjam while at lower solid content, shear thickening is governed by hydrocluster formation. However, it was found later by Lin et al 134 that contact forces also dictate continuous shear thickening (CST) as well where the solid content can be as low as 49%.…”
Section: Theories Of Shear Thickeningmentioning
confidence: 99%